Clinical characteristic and outcomes of pregnant women with COVID‐19: The PROUDEST prospective cohort study - Lizandra Paravidine Sasaki; Geraldo Magela Fernandes; Ângelo Pereira da Silva; Yacara Ribeiro Pereira; Aleida Oliveira de Carvalho; Felipe Motta; David Alves de Araújo Junior; Maria Eduarda Canellas de Castro; Gabriela Profírio Jardim-Santos; Heidi Luise Schulte; Clara Correia de Siracusa; Isadora Pastrana Rabelo; et al. (PLoS ONE, 2025)
The present study intended to characterize the clinical features and outcomes of SARS-CoV-2 infection at distinct pregnancy trimesters. A total of 260 pregnant women with SARS-CoV-2 infection at any pregnancy trimester were enrolled in a prospective follow-up study. Clinical features were recorded between the SARS-CoV-2 infection diagnosis towards delivery and postpartum period. ANOVA and Chi-square/Fisher tests, Bi- and multivariate analyses were performed to verify the effect of predictors on disease outcome, adjusted for the pregestational variables. Data demonstrated that anosmia (64.6%), nasal congestion/discharge (61.5%), headache (60.8%), ageusia (58.5%) and myalgia (58.5%) were the most common symptoms observed amongst pregnant women with non-severe COVID-19. Fever (44.6%) and dyspnea (36.5%) were associated with higher disease severity. Gestational diabetes mellitus (35.8%), systemic arterial hypertension (18.1%), preterm delivery (11.5%) and superimposed preeclampsia (6.2%) were reported as adverse pregnancy outcomes amongst pregnant women with COVID-19. Parturients with acute COVID-19 and pregnant women infected at the 3rd trimester presented more severe or critical outcomes as compared to those infected at 2nd and 1st trimesters. Preterm labor (Odds Ratio = 3.64), acute fetal distress (Prevalence Ratio = 2.40) and Apgar 1st minute score ≤ 7 (Prevalence Ratio = 2.56) were adverse outcomes reported in parturients with acute COVID-19 and those with severe or critical outcomes. Together these findings demonstrated that SARS-CoV-2 infection during pregnancy was associated with relevant maternal and neonatal adverse outcomes. The understanding of the clinical and obstetric outcomes of COVID-19 during pregnancy can provide insights to establish the most suitable approach for clinical management of pregnant women.